Fabrication of a Zircon Microfiltration Membrane for Culture Medium Sterilization - Zineb Khebli; Ferhat Bouzerara; Nourddine Brihi; Alberto Figoli; Francesca Russo; Francesco Galiano; Sadek Chahredine (Membranes, 2023)
Multilayer ceramic membranes to be used for bacteria removal by filtration were prepared from ceramic materials. They consist of a macro-porous carrier, an intermediate layer and a thin separation layer at the top. Tubular and flat disc supports were prepared from silica sand and calcite (natural raw materials), using extrusion and uniaxial pressing methods, respectively. Making use of the slip casting technique, the silica sand intermediate layer and the zircon top-layer were deposited on the supports, in this order. The particle size and the sintering temperature for each layer were optimized to achieve a suitable pore size for the deposition of the next layer. Morphology, microstructures, pore characteristics, strength and permeability were also studied. Filtration tests were conducted to optimize the permeation performance of the membrane. Experimental results show that the total porosity and average pore size of the porous ceramic supports sintered at different temperatures within the range (1150–1300 °C), and lie in the ranges of 44–52% and 5–30 μm, respectively. For the ZrSiO4 top-layer, after firing at 1190 °C, a typical average pore size of about 0.3 μm and a thickness of about 70 μm were measured, while water permeability is estimated to a value of 440 lh−1m−2bar−1. Finally, the optimized membranes were tested in the sterilization of a culture medium. Filtration results show the efficiency of the zircon-deposited membranes for bacteria removal; indeed, the growth medium was found to be free of all microorganisms.